Idiopathic and hereditary haemorrhagic telangiectasia associated pulmonary arteriovenous malformations: comparison of clinical and radiographic characteristics. Issue 5 (May 2021) - Kroon, S.; van den Heuvel, D.A.F.; Vos, J.A.; van Leersum, M.; van Strijen, M.J.L.; Post, M.C.; Mager, J.J.; Snijder, R.J.
Abstract : AIM: To determine whether there are differences between idiopathic and hereditary haemorrhagic telangiectasia (HHT) associated pulmonary arteriovenous malformations (PAVMs) (HHT-PAVM) regarding clinical and radiographic characteristics, and the results of embolotherapy. MATERIALS AND METHODS: A retrospective analysis was undertaken of all adult and adolescent patients who were diagnosed with a PAVM on chest computed tomography (CT) from January 2006 until August 2019. RESULTS: In total, 41 patients with idiopathic PAVMs and 194 patients with genetically confirmed HHT and PAVMs were included. Idiopathic PAVMs were more frequently observed in female patients, were more solitary, and predominantly located in the lower lobes. The diameter of the feeding artery and type of PAVM (simple versus complex) were similar. Embolotherapy results were comparable between both groups with similar re-embolisation rates. CONCLUSIONS: PAVMs of idiopathic origin are predominantly found in women, more frequently located in the lower lobes, and solitary compared to HHT-PAVMs; however, the outcome of treatment is the same, suggesting that treatment and follow-up should be similar in both groups. Highlights: In approximately 10% of patients with PAVMs no cause for the PAVM can be identified. Untreated PAVMs can result in stroke and brain abscess. Characteristics of idiopathic PAVMs were quite similar to HHT related PAVM. Embolotherapy results were comparable in idiopathic and HHT-PAVM.